2019
DOI: 10.22175/mmb.10724
|View full text |Cite
|
Sign up to set email alerts
|

Nix Pro Color Sensor Provides Comparable Color Measurements to Hunterlab Colorimeter

Abstract: ObjectivesMeat color is the most important quality attribute that influences consumer purchase decisions. Monitoring color to maximize shelf life and consumer acceptability is routinely used in meat science research. The HunterLab MiniScan EZ (HunterLab) colorimeter is the widely used industry standard for objectively measuring meat color. This device can collect tristimulus values of CIE L* (lightness), a* (redness), and b* (yellowness) for color measurements based on the light reflectance from the meat surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Since the inexpensive and smaller Nix colorimeter has been introduced, Schelkopf et al (2019) compared beef color using the HunterLab colorimeter and the Nix. Similarly, Holman et al (2018) measured the precision of technical replicates on aged beef using the Nix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the inexpensive and smaller Nix colorimeter has been introduced, Schelkopf et al (2019) compared beef color using the HunterLab colorimeter and the Nix. Similarly, Holman et al (2018) measured the precision of technical replicates on aged beef using the Nix.…”
Section: Discussionmentioning
confidence: 99%
“… Holman and Hopkins (2019) reported that the Nix did not provide comparable beef color values when compared to the HunterLab colorimeter due to higher L* values measured by the Nix. However, Schelkopf et al (2019) reported that Nix provided comparable color measurements to the HunterLab colorimeter when used to assess beef L* values. In the case of poultry meat, only limited research has been reported comparing these devices.…”
Section: Introductionmentioning
confidence: 99%